Differential Effects of Intrauterine Balloon Tamponade Indications on Postpartum Hemorrhage Outcomes - Xu, Chuangchuang; Chen, Yiyao; Wen, Lin; Chi, Xiaolei; Chen, Xinliang (Frontiers in Medicine, 2022)
Objective: To determine whether the indication of intrauterine balloon tamponade (IUBT) was associated with postpartum hemorrhage (PPH) outcomes. Methods: Patients with PPH who underwent IUBT between January 2013 and November 2021 were included in a cohort study. PPH outcomes in patients who had IUBT for indications of uterine atony were compared to those who had IUBT for indications of placental site bleeding. PPH outcomes included uterine artery embolization (UAE) or hysterectomy after IUBT, estimated blood loss (EBL) after balloon placement, and blood transfusion. Statistical analysis was performed using multivariate logistic regression. Results: IUBT was performed on 603 cases, with 121 (20.1%) undergoing it for placental site bleeding and 482 (79.9%) for uterine atony. In general, IUBT was a reliable treatment for PPH, but the specific efficacy varied depending on the indication for placement. After controlling for confounding variables, compared to the indication of uterine atony, the indication of placental site bleeding increased the risk of transfusion of ≥ 4 units of PRBCs (aOR 2.47, 95%CI 1.32–3.98), EBL ≥ 300 mL after IUBT (aOR 3.78, 95%CI 2.22–5.33), and UAE or hysterectomy (aOR 2.52, 95%CI 1.20–6.01), respectively. Other factors associated with adverse PPH outcomes were lower antenatal hemoglobin, higher IUBT volume, longer duration of IUBT and larger shock index values. Conclusions: IUBT was less effective in treating PPH patients with indications of placental site bleeding than with indications of uterine atony. Follow-up monitoring of PPH patients with placental site bleeding should be intensified.